Associations Between Maternal Immunisation and Reduced Rates of Preterm Birth and Stillbirth: A Population Based Retrospective Cohort Study - Giles, Michelle L.; Davey, Mary-Ann; Wallace, Euan M. (Frontiers in Immunology, 2021)
Stillbirth and preterm birth (PTB) remain two of the most important, unresolved challenges in modern pregnancy care. Approximately 10% of all births are preterm with nearly one million children dying each year due to PTB. It remains the most common cause of death among children under five years of age. The numbers for stillbirth are no less shocking with 2.6 million babies stillborn each year. With minimal impact on the rate of these adverse birth outcomes over the past decade there is an urgent need to identify more effective interventions to tackle these problems. In this retrospective cohort study, we used whole-of-population data, to determine if maternal immunization during pregnancy against influenza and/or pertussis, is associated with a lower risk of PTB, delivering a small-for-gestational age (SGA) infant, developing preeclampsia or stillbirth. Women with a singleton pregnancy at 28 or more weeks’ gestation delivering in Victoria, Australia from July 2015 to December 2018 were included in the analysis. Log-binomial regression was used to measure the relationship between vaccination during pregnancy against influenza and against pertussis, with preterm birth, SGA, preeclampsia and stillbirth. Variables included in the adjusted model were maternal age, body mass index, first or subsequent birth, maternal Indigenous status, socio-economic quintile, smoking, public or private maternity care and metropolitan or rural location of the hospital. Women who received influenza vaccine were 75% less likely to have a stillbirth (aRR 025; 95% CI 0.20, 0.31), and 31% less likely to birth <37 weeks (aRR 0.69; 95% CI 0.66, 0.72). Women who received pertussis vaccine were 77% less likely to have a stillbirth (aOR 0.23; 95% CI 0.18, 0.28) and 32% less likely to birth <37 weeks gestation (aRR 0.68; 95% CI 0.66, 0.71). Vaccination also reduced the odds of small for gestational age by 13% and reduced the odds of pre-eclampsia when restricted to primiparous women. This association was seen over four different influenza seasons and independent of the time of year suggesting that any protective effect on obstetric outcomes afforded by maternal vaccination may not be due to a pathogen-specific response but rather due to pathogen-agnostic immune-modulatory effects.